A AN ANALYSIS OF HERITAGE LEGAL LAW FOR FOREIGN NATIONAL HEIRS ON THE PERMANENT OBJECT (PROPERTY) BASED ON CIVIL LAW : AN ANALYSIS OF HERITAGE LEGAL LAW FOR FOREIGN NATIONAL HEIRS ON THE PERMANENT OBJECT (PROPERTY) BASED ON CIVIL LAW - Pandiangan, L.Elly AM (Advances in Social Sciences Research Journal, 2020)
In Indonesia, there is still no national legal entity regarding the inheritance law that can be applied to all Indonesian citizens. Therefore, the inheritance law that is applied to all Indonesian citizens is still different due to the classifications of the citizens. This study basically describes the inheritance rights of Foreign Citizens (foreigners) over fixed objects (treasure) especially the land in Indonesia. In the legal structure in Indonesia until now there has not yet been established national inheritance law provisions that regulate the rights of inheritance from foreign citizenship, while in the Basic Agrarian Law (UUPA) Law. No. 5 0f 1960, foreign nationals may not obtain ownership rights over land. Marriage law is legal, if it is done according to the law of each religion and belief as explained in article 2 paragraph (1) of law number 1 of 1974 concerning the marriage. Thus differences in citizens do not prevent a person from marrying and obtaining his inheritance rights, this difference in citizenship is a series of existing laws that are subject to customary law, how in terms of inheritance that are fixed objects will they be synchronized with International Civil Law (ICL) in obtaining objects that are usually done by way of buying and selling, grants, or by inheritance. The result of this study are the transfer of the inheritance of Foreign Citizens, especially regarding the land. Foreign citizens must relinquish their rights as heirs to the land, and within one year have to relinquish their rights. The rare several obstacles in the application of this law because there is no national inheritance law that regulates such cases because in religious and customary laws, there are no rules that limit the inheritance rights of foreign countries in Indonesia.